3-NOP: ADME studies in rats and ruminating animals. (March 2019) - Thiel, A.; Rümbeli, R.; Mair, P.; Yeman, H.; Beilstein, P.
Abstract: 3-NOP (3-nitrooxypropanol) reduces enteric methane formation in ruminants. A series of ADME studies in rats, lactating goats and beef cattle was performed. 3-NOP was entirely absorbed from the GIT of rats: approximately 75% of the administered 3-NOP was eliminated as carbon dioxide via exhalation and approximately 20% were excreted via urine. 3-NOP is oxidized to 3-nitrooxypropionic acid (NOPA) which is then hydrolyzed to 3-hydroxypropionic acid (HPA) and inorganic nitrate, the major rat plasma metabolites. NOPA is also a plasma metabolite in beef. The metabolism of 3-NOP is fast as indicated by the negligible amounts of 3-NOP found in rat plasma 2 h after dosing. HPA is a naturally occurring metabolite. It is either metabolized into carbon dioxide and acetyl-CoA or into propanoyl-CoA, the latter serves as substrate for gluconeogenesis. Gluconeogenesis is very prominent in lactating ruminants which use propanoyl-CoA as their main carbon source. Thus, the formation of lactose from 3-NOP by lactating goats is not unexpected. Lactose was the major metabolite of 3-NOP in the aqueous phase of milk. The incorporation of 3-NOP into endogenous metabolism makes it difficult to derive a marker residue, however, conservative risk assessment could be based on the measured radioactivity in tissues. Highlights: The majority of 3-NOP is metabolized into carbon dioxide. 3-NOP is metabolized into endogenous compounds. Xenobiotic residues are unlikely in aqueous phase of milk.